Experience of using long-acting testosterone undecanoate in hypogonadism, obesity and metabolic syndrome in men (Ожирение и метаболизм, 2013)
The paper outlines the author's experience on the efficacy and safety of androgen therapy of metabolic syndrome and obesity in men with hypogonadism. The study used testosterone undecanoate therapy that reduced body fat and the severity of the other components of the metabolic syndrome, improved sexual function without causing severe side effects. A number of patients on therapy observed suppression of spermatogenesis, which prevents the use of the drug in the reproductive rehabilitation.